FACTORISE : [ THERE SHOULD BE PROPER STEPS ]
![{4x}^{4} + {9y}^{4} + {11x}^{2} {y}^{2} {4x}^{4} + {9y}^{4} + {11x}^{2} {y}^{2}](https://tex.z-dn.net/?f=+%7B4x%7D%5E%7B4%7D++%2B++%7B9y%7D%5E%7B4%7D++%2B+++%7B11x%7D%5E%7B2%7D++%7By%7D%5E%7B2%7D+)
* NONSENSE ANSWERS WLL BE REPORTED
* ANSWERS WITHOUT STEPS WILL BE REPORTED
* CORRECT ANSWERS WILL BE MARKED BRAINLIEST
Answers
Answered by
1
As, in 3rd step
![{a}^{2} + {b}^{2} + 2ab = (a + b) {}^{2} {a}^{2} + {b}^{2} + 2ab = (a + b) {}^{2}](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D+%2B+%7Bb%7D%5E%7B2%7D+%2B+2ab+%3D+%28a+%2B+b%29+%7B%7D%5E%7B2%7D+)
![{a}^{2} + {b}^{2} = (a + b) {}^{2} - 2ab {a}^{2} + {b}^{2} = (a + b) {}^{2} - 2ab](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D+%2B+%7Bb%7D%5E%7B2%7D+%3D+%28a+%2B+b%29+%7B%7D%5E%7B2%7D+-+2ab)
In the last step it is( a+b) (a-b) =a square - b square
(.......) 2 - x square y square
=(.......) square - (xy) square
= Identity to be use is a square - b square =(a+b) (a-b)
Then, (....... +xy) (...... - xy)
In the last step it is( a+b) (a-b) =a square - b square
(.......) 2 - x square y square
=(.......) square - (xy) square
= Identity to be use is a square - b square =(a+b) (a-b)
Then, (....... +xy) (...... - xy)
Attachments:
![](https://hi-static.z-dn.net/files/de5/6ebe4292b66a25a668eddc3b9644d3a7.jpg)
PQRXTZ:
ok
Similar questions